Building Brand Image Through Price: An Effective Strategy To Enhance Purchasing Decisions - Pradono, Nuswantoro Setyadi; Sumastuti, Efriyani (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2025)
This study examines the relationship between pricing and customer purchase decisions and brand perception, as well as the role that promotion plays as a mediator. Using a quantitative, cross-sectional methodology, 100 marketplace users were given an online survey to complete in order to gather data. The measuring model and the structural relationships between the constructs—price, brand image, promotion, and purchasing decision—were assessed using partial least squares structural equation modeling, or PLS-SEM. The results demonstrate that price directly affects purchasing decisions and greatly enhances brand image. Brand image plays a significant role in influencing decisions about what to buy and somewhat mediates the relationship between pricing and buying decisions. Promotion improved brand image, which helped it indirectly even though it had no discernible direct impact on purchasing decisions. These results emphasize how price plays a strategic role in influencing consumer attitudes and behavior, and they also show how important brand image is as a mediator in this process. The study's cross-sectional design and narrow focus on just two marketing mix components limit how far the findings may be applied. Future studies should take into account longitudinal designs to record shifts in consumer views over time, as well as other variables like product quality and customer loyalty. By elucidating the mediating function of brand image in connecting pricing and promotion with purchase decisions, this study advances marketing theory. For practitioners looking to maximize price and promotional tactics to improve customer purchasing behavior, the conclusions drawn have useful ramifications.